Computer modeling: A gateway to novel advancements in solving real-life problems - Raza, Ali; Rafiq, Muhammad; Ahmed, Nauman; Iqbal, Muhammad Sajid; Rezapour, Shahram; İnç, Mustafa (Elsevier Sci Ltd, 2024)
The design of computer modelling has a vital role in the recent development of scientific literature. Creation, modification, analysis, and optimization of structures are uses of computer methods. The most significant benefit is communication through documentation, quality of design, designing electronic systems, and many more. According to the World Health Organization report, there are two types of transmission of Nipah virus infection, such as from animals to humans or humans to humans. More than 40% to 75% rate of death due to Nipah virus is estimated. The most infected regions are Thailand, the Philippines, Indonesia, and Cambodia. The susceptible (S), exposed (E), infected (I), and recovered (R) are compartments of the Nipah virus model. The bilinear incidence rates are considered during its modelling. Positivity, boundedness, equilibria, reproduction number, and stability results are part of the qualitative analysis of the model. After that, the design of the computer methods on the model predicts the efficiency, visualization, and results of the Nipah virus disease. The existing techniques, like Euler and Runge Kutta, could be more stable. They are highly time-dependent methods. But our proposed way, i.e., NSFD, is always positive, bounded, regular and consistent at any time step size. In conclusion, the nonstandard finite difference method (NSFD) restores a dynamical property such as positivity, boundedness, consistency, and stability. In the end, computing techniques are presented to support the qualitative analysis of the model.
Keywords: Nipah virus; Epidemic model; Computing methods; Linearization analysis